The Influence Of Online Service Quality And Work Environment On The Level Of Customer Satisfaction At UPTD KIR At The South Solok LH And Transportation Department - Safitri, Dewi Novitas; Bismark, O. P.; Sovia, Arina; Wandra, Novera; Bismark, Irma Auliyah (Strata International Journal of Social Issues, 2024)
This research aims: (1) To describe online service quality, work environment, and customer satisfaction, (2) to determine the effect of online service quality on customer satisfaction (3) to determine the influence of the work environment on the level of customer satisfaction (4) to determine the effect of online service quality and work environment on customer satisfaction at UPTD (Regional Technical Test Unit) at the South Solok Regency Environmental and Transportation Settlement Area Housing Service. The research design is descriptive and causal. Data analysis used Multiple Regression Analysis with the SPSS for Windows 23 computer program. Online services have a significant influence on satisfaction. This shows that the work environment significantly influences the level of customer satisfaction at UPTD KIR at the Housing Service for the Environment and Transportation Settlement Area of South Solok Regency. (3) The work environment significantly affects the level of customer satisfaction. This shows that the work environment significantly affects the level of customer satisfaction at UPTD KIR at the Housing Service for the Environment and Transportation Settlement Areas of South Solok Regency. (4) The results of the first test from the Anova test or F test can be drawn. This means there is a significant influence between the online service quality variables and the work environment together on the level of customer satisfaction at UPTD KIR.